Evaluation of Pesticides for Carcinogenic Potential - Frederick M. Fishel (EDIS)
The purpose of this guide is to discuss the 5-tiered scheme used by the Environmental Protection Agency (EPA) to classify the carcinogenic potential of pesticides. This document is PI-37, one of a series of the Pesticide Information Office, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published April 2005.